Development of 3D Simulation Application for Production Multimedia Subject - Muhammad Syazwan Mohd Januri; Abu Bakar Ibrahim; Azman Salleh; Marzuki Hussain (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
The development of 3D simulation applications for Production of Multimedia Subjects is intended to provide exposure and convenience to teachers, especially prospective teachers of Universiti Pendidikan Sultan Idris in exploring the 3D virtual world of the classroom and school environment in the context of learning and facilitate teachers to obtain daily information in finding relevant information. 3D. The objective of this study is to identify the 3D elements needed to build a school environment, design and develop a virtual reality application simulation application program that can be developed and evaluate the function of this 3D simulation application can help teachers teach and learn in schools. In addition, the use of applications such as simulators is basically for research and educational purposes. This study uses the ADDIE model used in the development of a 3D simulation application for this Multimedia Production subject. Simulation is capable of producing a virtual world of the surrounding atmosphere and a real environment. This Multimedia Production subject learning simulation can give students an idea of the learning environment in school. There is no denying that the use of simulation applications is not widespread as most of the available applications mostly focus on skills such as aeroplane piloting. With this, applications such as simulators are developed to give students an experience of the virtual learning environment.